2015
DOI: 10.1152/japplphysiol.00223.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperoxic and hyperbaric conditions on the adenosinergic pathway and CD26 expression in rat

Abstract: The nucleoside adenosine acts on the nervous and cardiovascular systems via the A2A receptor (A2AR). In response to oxygen level in tissues, adenosine plasma concentration is regulated in particular via its synthesis by CD73 and via its degradation by adenosine deaminase (ADA). The cell-surface endopeptidase CD26 controls the concentration of vasoactive and antioxidant peptides and hence regulates the oxygen supply to tissues and oxidative stress response. Although overexpression of adenosine, CD73, ADA, A2AR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…Our results and previous studies support the fact that APL is generated in an oxygen-dependent manner (Schrader et al, 1990). Indeed, it has been reported that hypoxia induced an increase in APL (Eltzschig et al, 2006;Joulia et al, 2013) whereas hyperoxia lead to a decrease in APL (Bruzzese et al, 2015;Fromonot et al, 2016). The impact of adenosine on the hemodynamic status is well recognized and could contribute to the cardio-vascular changes observed in our healthy volunteers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results and previous studies support the fact that APL is generated in an oxygen-dependent manner (Schrader et al, 1990). Indeed, it has been reported that hypoxia induced an increase in APL (Eltzschig et al, 2006;Joulia et al, 2013) whereas hyperoxia lead to a decrease in APL (Bruzzese et al, 2015;Fromonot et al, 2016). The impact of adenosine on the hemodynamic status is well recognized and could contribute to the cardio-vascular changes observed in our healthy volunteers.…”
Section: Discussionsupporting
confidence: 91%
“…A decrease in muscle sympathetic nerve activity has been reported at rest but not during exercise (Seals et al, 1991). Recently, a decrease in adenosine plasma levels (APLs) has been reported in rats subjected to normobaric or hyperbaric hyperoxia (Bruzzese et al, 2015). Adenosine is an ATP derivative which strongly impacts heart rate and blood pressure through its G-protein coupled receptors known as A1, A2A, A2B, or A3R, depending on their pharmacological properties (Burnstock, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms underlying this response may involve a down-regulation of the adenosine pathway [28] or modulation of the ROS-mediated prostaglandin and NO pathways [29] with reduced NO bioavailability [30]. In our study, hyperoxia led to an early decrease in microcirculatory vessel density and perfusion after 2 min of exposure.…”
Section: Discussionmentioning
confidence: 68%
“…A large number of human CNS disease studies have implicated adenosine 2A receptors (A 2A ), including schizophrenia [192], Pick's disease [193], MCI [194], bipolar disorder [195], and HD [196], and additionally in pre-clinical models of AD [197], addiction [198], aging [199], attention deficit hyperactivity disorder [200], epilepsy [201], hyperoxia [202], multiple sclerosis (MS) [203], PD [204], restless leg syndrome [205], and tauopathy [206], amongst others. For in-depth reviews, refer to Waarde et al [207] and Cheffer et al [208].…”
Section: Adenosine a 2amentioning
confidence: 99%